PERTANGGUNGJAWABAN PIDANA MAFIA TANAH DALAM TINDAK PIDANA KORUPSI DI BALI - I Nyoman Suardiana; A.A. Gde Putra Arjawa; I Nyoman Suandika (Yayasan Nusantara Hasana Berdikari, 2023)
The purpose of this study is to determine the criminal responsibility of the land mafia in corruption crimes and to know how to prevent land mafia crimes in corruption crimes. The method used in the preparation of this research is a juridical-normative approach, namely a study that focuses or examines the application of legal norms or rules in positive law. In addition, juridical-normative research focuses on library materials and regulations used as basic materials for preparation. The result of this study is that land mafia cases can be included in corruption crimes because some unscrupulous state officials or government employees take actions that utilize their authority to falsify state documents in the form of land certificates. This is able to make the land mafia can easily conduct land transactions. The methods used by the land mafia include; a. Falsification of documents (for rights); b. Legalization in court; c. Legitimate or unjust (wild) occupation; d. Incident engineering; e. Collusion with unscrupulous officials to obtain legality; f. Crimes with corporations such as embezzlement and fraud; g. Changes in land rights and loss of land warrants. There are five reasons for the existence of the land mafia, including; a. Lack of supervision; b. Lack of law enforcement; c. Lack of transparency; d. Land is a profitable investment; e. Have high economic value Land that is the need of the community. The practice of land mafia in the criminal act of corruption can be prevented if the landowner does not leave his land in a state of not having a land deed and land certificate. The community can go through BPN to take care of their land deed which then goes to a notary to make their land certificate. This is able to prevent the practice of land mafia against vacant land that has not been used.